Swimming Energy Economy in Bottlenose Dolphins Under Variable Drag Loading - van der Hoop, Julie M.; Fahlman, Andreas; Shorter, K. Alex; Gabaldon, Joaquin; Rocho-Levine, Julie; Petrov, Victor; Moore, Michael J. (Frontiers in Marine Science, 2018)
Instrumenting animals with tags contributes additional resistive forces (weight, buoyancy, lift and drag) that may result in increased energetic costs; however, additional metabolic expense can be moderated by adjusting behaviour to maintain power output. We sought to increase hydrodynamic drag for near-surface swimming bottlenose dolphins, to investigate the metabolic effect of instrumentation. In this experiment, we investigate whether (1) metabolic rate increases systematically with hydrodynamic drag loading from tags of different sizes or (2) whether tagged individuals modulate speed, swimming distance and/or fluking motions under increased drag loading. We detected no significant difference in oxygen consumption rates when four male dolphins performed a repeated swimming task, but measured swimming speeds that were 34% (>1 m s-1) slower in the highest drag condition. To further investigate this observed response, we incrementally decreased and then increased drag in six loading conditions. When drag was reduced, dolphins increased swimming speed (+1.4 m s-1; +45%) and fluking frequency (+0.28 Hz; +16%). As drag was increased, swimming speed (-0.96 m s-1; -23%) and fluking frequency (-14 Hz; 7%) decreased again. Results from computational fluid dynamics simulations indicate that the experimentally observed changes in swimming speed would have maintained the level of external drag forces experienced by the animal. Together, these results indicate that dolphins may adjust swimming speed to modulate the drag force opposing their motion during swimming, adapting their behaviour to maintain a level of energy economy during locomotion.